Dialektika Nilai Spiritual dan Tantangan Global: Rekonstruksi Zuhud, Sabar, dan Ikhlas di Era Digital - Adhi Danar Dono; Lalang Dintara; Agus Setiawan; Triana Ambarwati; Ismail Mubarok (JURNAL ILMIAH NUSANTARA, 2026)
This study conducts a conceptual reconstruction of three Islamic spiritual values—namely, zuhud, sabar, and ikhlas with the aim of fostering Islamic character among the younger generation. The method employed is a critical literature review with an analytical hermeneutic synthesis of scholarly works published over the past five years. The analysis highlights interpretive disagreements among experts regarding the ontological and practical dimensions of these values, and identifies research gaps that have not been extensively explored, particularly regarding the integration of spiritual values into character education curricula. The results of the synthesis indicate that while there is consensus on the importance of these three values, significant differences emerge regarding the interpretation of zahir batin (zuhud), the psychological mechanisms of patience, and the context of sincerity in social practice. This study offers an original contribution in the form of a conceptual map that can serve as a foundation for the development of a character education model based on modern Sufism.